Complexation of Rh(III) in sulfuric acid solutions - A. V. Belyaev; M. A. Fedotov; S. N. Shagabutdinova; E. I. Pavlova (Тонкие химические технологии, 2007)
The complexation in the system Rh(III) – H2SO4 – H2O at the room temperature in the dilute sulfuric acid has been studied by 103Rh and 17O NMR. The most stable species in solutions are [Rh2(μ-SO4)2(H2O)8] 2+ and [Rh2(μ-OH)(μ-SO4)(H2O)8] 3+; we have established that the solid «rhodium sulfates” are amorphous glassy phases with variable composition